Investigating the association between SARS-CoV-2 infection, COVID-19 vaccination, and autoimmune diseases in a pediatric population: a comprehensive analysis - Cynthia Freiberg; Arad Dotan; Dana Arnheim; Yonatan Butbul Aviel (Pediatric Rheumatology Online Journal)
Abstract Background During the COVID-19 pandemic there were reports of an increased association between COVID 19 and various autoimmune diseases (AID) in adults. This study aims to investigate the incidence of AIDs in children before and during the pandemic and explores potential links to SARS-CoV-2 vaccination. Methods We analyzed 493,705 anonymized medical records from Maccabi Healthcare Services, Israel’s second-largest healthcare provider, to study AID incidence during 2014–2022. The study period was divided into three phases: two pre-pandemic phases of equal duration (A and B) and a pandemic phase (C). Results Of 4,596 (0.9%) patients diagnosed with an AID in the cohort, incidence rates were 0.9% for Group A (2014–2016), 1.0% for Group B (2017–2019), and 0.9% for Group C (2020–2022) (p = 0.13). Logistic regression showed no significant differences in overall autoimmune disease incidence between the pre-COVID and COVID periods. Notably, specific conditions like celiac disease showed reduced incidence in Group A (OR 0.8309, p = 0.0071) while arthritis was significantly more common in Groups A and B. Additionally, COVID-19 diagnosis was not significantly associated with increased autoimmune disease risk (HR 1.092, p = 0.491); however, receiving at least one COVID vaccine was linked to higher risk (HR 1.2323, p = 0.0033). Conclusion Our findings suggest that the overall incidence of new-onset autoimmune diseases in children remained relatively stable during the COVID-19 pandemic. The study indicates a potential association between COVID-19 vaccination and an increased risk of developing autoimmune diseases, necessitating further research to elucidate long-term effects in the pediatric population.